The Rise of the Middle Class in the People's Republic of China - Zhang Yuan; Guanghua Wan; Niny Khor (Asian Development Bank (ADB), 2011)
Using dollar2–dollar20 purchasing power parity per capita daily income as the definition of middle class, Zhang Yuan, Guanghua Wan, and Niny Khor find that majority of households in the People's Republic of China have become middle class by 2007. This is especially impressive given that around 40% of households were still considered poor in 1991. This paper discusses these trends, their main determinants, and geographical distributions.
hdl:11540/2043
Keywords: 330; Mittelschicht; Soziale Mobilität; Industrialisierung; Privatisierung; China